Head Motion Predicts Transient Loss of Consciousness in Human Head Trauma: A Case-Control Study of Mixed Martial Artists. (October 2019) - Fogarty, Alexandra E.; Guay, Christian S.; Simoneau, Gabrielle; Colorado, Berdale S.; Segal, G. Ross; Werner, J. Kent; Ellenbogen, Jeffrey M.
Abstract : Objective: Concussion with transient loss of consciousness is a commonly observed but poorly understood phenomenon with mounting clinical significance. This study aimed to examine the relationship between head motion in varying planes and transient loss of consciousness in athletes with brain injuries. Study Design: A case-control design was used. The Ultimate Fighting Championship database was screened for events ending with knockouts from 2013 to 2016. Time of strike, striking implement, strike location, and head motion were recorded for all knockout strikes (cases) and for a subset of nonknockout strikes (controls). Characteristics of winners and losers were compared using two-tailed t tests. Multivariate logistic regression was used to determine odds ratios for strike characteristics associated with transient loss of consciousness. The Kaplan-Meier estimate was used to describe the temporal distribution of knockouts. Results: One hundred thirty-six fights were identified and 110 videos were included. Head motion in the axial plane was strongly associated with transient loss of consciousness (odds ratio, 45.3; 95% confidence interval, 20.8–98.6). Other predictors of transient loss of consciousness were head motion in sagittal and coronal planes, nonfist striking implements, and strikes to the mandible or maxilla. The Kaplan-Meier survival curve demonstrated a decreasing rate of knockouts through time. Conclusions: Rotational head acceleration, particularly in the axial plane, is strongly associated with transient loss of consciousness.